Neoadjuvant therapy versus direct to surgery for T4 colon cancer: meta-analysis. Issue 1 (17th December 2021) - Jung, Flora; Lee, Michael; Doshi, Sachin; Zhao, Grace; Cheung, Kimberley Lam Tin; Chesney, Tyler; Guidolin, Keegan; Englesakis, Marina; Lukovic, Jelena; O'Kane, Grainne; Quereshy, Fayez A; Chadi, Sami A
Abstract: Background: Despite persistently poor oncological outcomes, approaches to the management of T4 colonic cancer remain variable, with the role of neoadjuvant therapy unclear. The aim of this review was to compare oncological outcomes between direct-to-surgery and neoadjuvant therapy approaches to T4 colon cancer. Methods: A librarian-led systematic search of MEDLINE, Embase, the Cochrane Library, Web of Science, and CINAHL up to 11 February 2020 was performed. Inclusion criteria were primary research articles comparing oncological outcomes between neoadjuvant therapies or direct to surgery for primary T4 colonic cancer. Based on PRISMA guidelines, screening and data abstraction were undertaken in duplicate. Quality assessment was carried out using Cochrane risk-of-bias tools. Random-effects models were used to pool effect estimates. This study compared pathological resection margins, postoperative morbidity, and oncological outcomes of cancer recurrence and overall survival. Results: Four studies with a total of 43 063 patients met the inclusion criteria. Compared with direct to surgery, neoadjuvant therapy was associated with increased rates of margin-negative resection (odds ratio (OR) 2.60, 95 per cent c.i. 1.12 to 6.02; n  =   15 487) and 5-year overall survival (pooled hazard ratio 1.42, 1.10 to 1.82, I 2  = 0 per cent; n  =   15 338). No difference was observed in rates of cancer recurrence (OR 0.42, 0.15 to 1.22; n  =   131), 30-day minor (OR 1.12, 0.68 to 1.84; n  =   15 488) or major (OR 0.62, 0.27 to 1.44; n  =   15 488) morbidity, or rates of treatment-related adverse effects. Conclusion: Compared with direct to surgery, neoadjuvant therapy improves margin-negative resection rates and overall survival. Abstract : The objective of this systematic review was to compare oncological outcomes between direct-to-surgery (DTS) and neoadjuvant therapy (NAT) approaches to T4 colonic cancer. Compared with the DTS approach, NAT improves rates of margin-negative resection and overall survival.